A microfluidics platform for combinatorial drug screening on cancer biopsies - Eduati, Federica; Longerich, Thomas; Sáez Rodríguez, Julio (Nature Communications, 2018)
Cancer patients exhibit specific sensitivities toward drug combinations that cannot be easily predicted. Here the authors setup a microfluidic platform that allows testing of multiple drug combinations correctly predicting sensitivity in vivo and they use it on patients biopsies to define effective drugs.